STUDY USE POWDER AS RAW MATERIALS MANUFACTURING SAWS INSULATOR COOLING BOX FISH (COOLBOX) USED TRADITIONAL FISHERMEN - Kholis, Muhammad Natsir; Syofyan, Irwandy; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted on 3-14 July 2014 in the laboratory of Materials Capture Tool (BAT) Department of Water Resource Utilization (PSP). The purpose of this study to determine sawdust as raw material for the manufacture of insulating and find the best composition to a predetermined ratio. The method used is the experimental method. Which conducted tests on three coolers of fish (coolbox) are made, with the insulator sawdust mixed with tapioca flour and then the data in anilisis descriptively. The result showed that the use of sawdust as raw material for the insulator can be used but need to be refined and modified to be able to compete with factory-made quality. Of the three treatments cooler box fish (coolbox) that retain the best of the old aspect ratio of ice is 100% sawdust for 12-13 hours. While the temperature of the best aspect ratio is 70:30 with the lowest temperature of 6.6 0C inner wall and outer wall of 20.4 0C.Keywords: Cooler Box Fish (coolbox). Insulator (insulation). Temperature